Distribution and classification of pockmarks on the seabed around western Scotland. Issue 2 (3rd July 2019) - Audsley, Allan; Bradwell, Tom; Howe, John A.; Baxter, John M.
ABSTRACT: Pockmarks are seabed depressions that represent primary evidence of rapid biogenic/thermogenic gas build up and fluid release from seabed sediments to the water column. We use a Geographical Information System (GIS) to analyse multibeam echo-sounder bathymetric data and use a range of semi-automated tools to map seabed pockmarks in fjords and adjacent coastal waters around western Scotland. We map 1019 individual pockmarks in 12 different hydrographic areas covering ca. 2019 km 2 . We use morphological metrics and statistical procedures to classify and analyse the variety of pockmark forms. A k-means clustering algorithm identifies three classes of pockmark morphology: deep, elongate and regular. The recognition of separate pockmark classes could aid understanding of their age, activity and origin. This work presents the first detailed mapping of pockmark fields in Scottish west coast waters and highlights the use of pockmarks as an indicator of the quantity, mobility and fate of stored carbon.